2007
DOI: 10.1002/asia.200700051
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Thermally Stable, Cholesteric Liquid‐Crystalline Helical Polyisocyanides with Memory of Macromolecular Helicity

Abstract: The achiral sodium salt of poly(4-carboxyphenyl isocyanide) (poly-1-Na) folds into a one-handed helix induced by optically active amines in water. The induced helicity remains when the optically active amines are completely removed, and further modification of the side groups to amide residues is possible without loss of memory of macromolecular helicity. Although the helical poly-1-Na loses its chiral memory at high temperature, helical polyisocyanides modified with achiral primary amines, which no longer hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 82 publications
0
31
0
Order By: Relevance
“…Taking advantage of this unique and versatile 'static' helicity memory effect, further modifications of side groups with a variety of functional groups of the polyisocyanide are possible without any loss of the macromolecular helicity memory, and the resulting modified polyisocyanides showed cholesteric LC phases (Figure 6c). 70,71 XRD of the uniaxially oriented film of the methyl ester of helical 27 (h-27-Me) prepared from its cholesteric LC polymer solution after helicity induction and memory suggests that the most plausible helical structure of h-27-Me is a 10/3 helix (Figure 6d). 69 The density functional theory calculations of poly(phenyl isocyanide), a model polymer of h-27-Me, showed a 7/2 helix as the most possible helical structure; this calculated helical structure can explain the XRD results.…”
Section: Helical Structure Determination Of Liquid Crystalline Helicamentioning
confidence: 99%
“…Taking advantage of this unique and versatile 'static' helicity memory effect, further modifications of side groups with a variety of functional groups of the polyisocyanide are possible without any loss of the macromolecular helicity memory, and the resulting modified polyisocyanides showed cholesteric LC phases (Figure 6c). 70,71 XRD of the uniaxially oriented film of the methyl ester of helical 27 (h-27-Me) prepared from its cholesteric LC polymer solution after helicity induction and memory suggests that the most plausible helical structure of h-27-Me is a 10/3 helix (Figure 6d). 69 The density functional theory calculations of poly(phenyl isocyanide), a model polymer of h-27-Me, showed a 7/2 helix as the most possible helical structure; this calculated helical structure can explain the XRD results.…”
Section: Helical Structure Determination Of Liquid Crystalline Helicamentioning
confidence: 99%
“…This precise architectural definition has been utilised in their application in electronic applications 7 . We found that a family of water-soluble thermoresponsive oligo(ethylene glycol) functionalized PICs is able to gel water with an extraordinary high efficiency [8][9][10] . Such hydrogel materials are very attractive in, for instance, the fields of drug delivery 11 , regenerative surgery 12 and advanced stimuli-responsive systems 13,14 .…”
mentioning
confidence: 99%
“…The induced helicity remains after the optically active amines are completely removed (helicity ''memory'') and further modifications of the side groups to amide residues can be possible without any loss of the macromolecular helicity memory. 25,28 A large number of helical polyisocyanides with functional pendant groups have been prepared, but their applications to chiral catalysts for an asymmetric reaction have not been reported. [29][30][31][32][33][34][35][36][37] We anticipated that the optically active poly(4-carboxyphenyl isocyanide) with a macromolecular helicity memory (h-poly-1-H) might be a promising scaffold for the development of diverse asymmetric polymer catalysts because further chemical modification of the carboxylic acid pendants with a variety of functional groups can be possible through an amide linkage to the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28] Poly(4-carboxyphenyl isocyanide) (poly-1-H) and its sodium salt (poly-1-Na) are achiral, but fold into a one-handed helix induced by optically active amines in water. The induced helicity remains after the optically active amines are completely removed (helicity ''memory'') and further modifications of the side groups to amide residues can be possible without any loss of the macromolecular helicity memory.…”
Section: Introductionmentioning
confidence: 99%